Fluoride Release from Glass Ionomer with Nano Filled Coat and Varnish - Valentina Brzović Rajić; Ivana Miletić; Sevil Gurgan; Kristina Peroš; Željko Verzak; Ana Ivanišević Malčić (Acta Stomatologica Croatica, 2018)
Objective: This in vitro study compares the fluoride release from microlaminated glass ionomer based on glass hybrid technology coated with two different surface coating agents. Materials and Methods: A total of 18 samples were divided into three groups of six samples each: (1) glass ionomer Equia Forte Fil coated with Equia Forte Coat (Equia+EC), (2) glass ionomer Equia Forte Fil coated with GC Fuji Varnish (Equia+VC) and (3) uncoated glass ionomer Equia Forte (EQUIA cont). Fluoride release was measured using an ion-selective electrode (ORION EA 940) after 24 hours, 4 days, 30 days and 64 days. Repeated measures ANOVA, multiple comparisons, Tukey’s test and paired t-test were used to test the differences between the groups. Results: The differences between the groups and four time points were statistically significant (ANOVA, p<0.0001). Cumulative fluoride ion release after 64 days was 66.01 mg/l, 123.54mg/l and 203.22 mg/l for EQUIA+EC, EQUIA+VC and EQUIA cont, respectively. All the differences were statistically significant except the difference between EQUIA+VC and EQUIA cont after 24 hours. Conclusions: The amount of released fluoride was significantly lower in the samples coated with nanofilled surface coating agent compared to the samples coated with varnish and uncoated samples.